Developing Josephson junction array chips for microvolt applications - 曹文会 李劲劲 钟源 高原 李红晖 王曾敏 贺青 (Chinese physics B, 2016)
Josephson junction array chips for microvolt applications have been designed and fabricated. A voltage step as small as 1 μV has been observed for a single junction in the array when it is driven by 483.59 MHz microwave. By selecting different parts of the array, it can output a voltage from 1 μV to 256 μV. The flat region of the voltage steps is over 200 μA.This kind of array is useful for potential microvolt applications.